Information Technology in Bio- and Medical Informatics Second International Conference, ITBAM 2011, Toulouse, France, August 31 - September 1, 2011, Proceedings - Böhm, Christian.; Böhm, Christian.; Khuri, Sami.; Khuri, Sami.; Lhotská, Lenka.; Lhotská, Lenka.; Pisanti, Nadia.; Pisanti, Nadia. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2011)
This book constitutes the thorougly refereed proceedings of the Second International Conference on Information Technology in Bio- and Medical Informatics, ITBAM 2011, held in Toulouse, France, in August/September 2011, in conjunction with DEXA 2011. The 13 long papers and 5 short papers were carefully selected and address the following topics: decision support and data management in biomedicine; medical data mining and information retrieval; workflow management and decision support in medicine; and classification in bioinformatics. The papers show how broad the spectrum of topics in applications of information technology to biomedical engineering and medical informatics is.